(untitled) (Philological Studies, 2019)
The fall of the empire in Serbian and Bulgarian traditional culture is always stylized as a fateful event, the end of the world. Since the empire is in a direct relationship with transcendence, its fall is foretold by prophecies. Having that in mind, the goal of this paper is to show the manifestational forms of prophecies about the end of the world, their semantic field and the images they mediate, through a poetical / aesthetical analysis of pieces of Serbian and Bulgarian epos that thematize the fall of the empire. While interpreting the conceptual role of prophecies within the complex of given themes and motifs, we will also examine their metahistorical, ontological orientation.